Kajian Fitokimia dan Aktivitas Antioksidan Jamur Tiram Putih (Pleurotus ostreatus) - Vritta Amroini Wahyudi; Laurent Octaviana; Sutrisno Sutrisno (Universitas Muhammadiyah Malang, 2020)
Processed products derived from mushrooms have been found and enjoyed by the community. One of the edible mushrooms used as traditional medicinal ingredients andalso, functional food is oyster mushrooms. Although oyster mushrooms have often been studied even using sophisticated instruments, some chemical laboratories that do not yet have sophisticated instruments still need literature data in the process of separation until pure isolates are obtained. This research was conducted to be the solution. The study uses descriptive methods by collecting data from the results of extraction, characterization, identification, and testing of antioxidant activity. Characterization includes retention factor (Rf) from elution of thin-layer chromatography (TLC), determination of melting point (to determine the purity of isolates), and solubility test (to determine the nature of polarity). The identification of isolates was done by analyzing the results of Infrared and UV-Vis spectra. Phytochemical studies of white oyster mushrooms can be done based on secondary metabolite screening, separation by extraction, and fractionation using organic solvents. Based on phytochemical screening, white oyster mushrooms are known to positively contain flavonoids, alkaloids, and terpenoids. The crude extract had an absorbance of 0.669 at 274 nm, the chloroform fraction had an absorbance of 0.827 at 267 nm, and pure isolates had an absorbance of 0.628 at 282 nm. A spectrum with a maximum wavelength of> 210 nm indicates a conjugated system. The longer the conjugated system, the more inactive in the UV region of 200- 360 nm (UV) but more active in the 360-729 nm (Visible) region (Worsfold et al, 2019). UV-Vis spectrum of methanol extract, chloroform fraction, and pure isolate showed wave crests in the region> 210 nm so that all three were shown to have a conjugated system.